An Investigation on the Intralocality Differences in Health and Safety Implementation of Construction Industries (Recoletos Multidisciplinary Research Journal, 2019)
Generally, the status of health and safety in the construction sector is reported to be declining. Consequently, this indicates the necessity of developing an awareness and a comprehensive knowledge among the role of various stakeholders in their contribution to construction health and safety improvement. As part of the construction industry stakeholders, the role of localities is one of the factors to consider in the formation of construction health and safety knowledge and practice. Despite the plethora of construction health and safety studies found in the literature, there have been very few studies that have considered the association between localities and their association with construction health and safety practices. In this paper, a Chi-square test of independence is used to investigate whether a disparity between localities and their safety practices exists. Moreover, this study contributes to existing literature in such a way that it is the first to consider the relationship between intra-locality and health and safety practices in the context of the construction industry. Furthermore, this study will be valuable for construction stakeholders in the formulation of a more unified and standardized health and safety practices and regulations.
Keywords: health and safety; construction industry; intralocality differences